Relationship Between Transformational Leadership and Organizational Commitment of the Cafe Employees - Dewi Lusita; Nur Pratiwi Noviati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2016)
This study attempt to search the relationship between transformational leadership and organizational commitment of the café employees. The hypotesis tested which based on the assumption that higer transformational leadership was correlated with higer organizational commitment. A subject of 58 employees were selected for this study. Employees included server, production, managers. Data were collected by the Transformational Leadership Questionare based aspects proposed by Bass (1990) and a=0,879 Organizational Commitment Questionare was modificaton from Allen and Meyer (1990) and a=0,884. This study analysis used Product moment correlation by Pearson. The analysis showed that there is significant relationship between transformasional leadership and organizational commitment p=0.004 (p<0.05). Result showed in an increasing the transformational leadership then increasing organizational commitment the employee to work. This is important to increase productivity an efficiency in an organization. Based on the results of the research, the research hypothesis is accepted. Keywords: Transformational Leadership, Organizational Commitment, Café